2013
DOI: 10.3324/haematol.2013.083642
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of wild-type survivin is associated with constitutive activation of the PI3K/Akt signaling pathway and represents a favorable prognostic factor in patients with acute myeloid leukemia

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n 2 0 1 3and proliferative effects partially by increasing survivin levels through PI3K activation in AML. 15 Additionally, it has been shown in a mouse model that internal tandem duplication of Flt-3 regulates survivin expression via PI3K/Akt leading to aberrant progenitor cell proliferation. 16 Although the importance of the PI3K/Akt/survivin pathway has been reported in lung and colon cancer, 17,18 its incidence and prognostic impact in AML have not been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…High levels of survivin are detected in many hematological malignancies, including leukemia [47]. Furthermore, it has been found that survivin expression is regulated through MAPK/ERK-dependent mechanisms and induced through PI3K/AKT signaling pathway in leukemia cells [48,49]. In the present study, survivin levels were significantly decreased in REH and MOLT-4 cells after combined treatment with AZD0364 and ZSTK474.…”
Section: Discussionsupporting
confidence: 51%
“…High levels of survivin are detected in many hematological malignancies, including leukemia [47]. Furthermore, it has been found that survivin expression is regulated through MAPK/ERK-dependent mechanisms and induced through PI3K/AKT signaling pathway in leukemia cells [48,49]. In the present study, survivin levels were significantly decreased in REH and MOLT-4 cells after combined treatment with AZD0364 and ZSTK474.…”
Section: Discussionsupporting
confidence: 51%
“…The most distinctive feature of survivin is involvement in cell death regulation. This nodal protein cannot directly interact with [ 30 ] caspases; it associates with X-linked IAP to repress caspase-dependent apoptotic pathway. Owing to its pivotal role in anti-apoptotic effects as well as promotion of cancer cell invasion and migration, survivin can be considered as a noticeable prognostic and metastatic factor in cancerous cells [ 31 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its pivotal role in anti-apoptotic effects as well as promotion of cancer cell invasion and migration, survivin can be considered as a noticeable prognostic and metastatic factor in cancerous cells [ 31 ] . Several lines of evidence made it apparent that high BIRC5 expression is associated with substantially inferior, poor, and adverse clinical outcome in AML [ 12 , 13 , 30 , 31 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The emerging body of evidence indicates that survivin acts as anti-apoptotic protein, as well as the promotion of cancer cell invasion and migration, implying that survivin can be considered as a noticeable prognostic and metastatic factor in cancerous cells 21. Several lines of evidence made it apparent that high BIRC5 expression has been associated with substantially inferior, poor, and adverse clinical outcome in AML 10,11,22,23…”
Section: Discussionmentioning
confidence: 99%